Consumer Engagement in Fudgybro's “Cookie Bomb Challenge” Viral Marketing - Eka Candelia, Dera; , Nikmah Hadiati Salisah (Lingkar Studi Komunikasi (LISKI), 2025)
Advertising is one of the main factors in making a brand famous and attractive to the public. However, with changing times, there is a need for innovation so that the advertisements produced can be considered creative and successful in attracting consumers' attention. Through social media, which currently has a big role in changing consumers' views of a brand. As for presenting an advertisement or marketing a product, there needs to be a strategy. The viral marketing strategy is the one most widely used by companies to introduce their brand. However, viral marketing certainly has a dependency on consumers who will be the support in producing content that goes viral. The Fudgybro brand is one brand that uses a viral marketing strategy that involves consumers in most of its content. Using the literature study research method helps researchers study a phenomenon that is analyzed using concepts that have been described in the literature. Based on the research carried out, the results obtained are that the Fudgybro Brand actively involves consumers to create viral marketing, starting with holding the "Cookie Bomb Challenge" so that it can reach not only Fudgybro's own social network, but also the environment of every consumer. Therefore, to produce a brand that can reach a wider reach, it is necessary to have an appropriate strategy to meet the targets of the brand itself. This study highlights the novelty of consumer-generated viral marketing through participatory digital culture, where consumers act not only as message recipients but also as active co-creators of brand content. The contribution of this research lies in demonstrating how consumer engagement and co-created experiences can strengthen brand awareness and purchase intention, expanding the understanding of viral marketing within communication studies.Keywords: advertising; creative; viral marketing; consumers.